PARTISIPASI POLITIK PESERTA SEKOLAH KADER PENGAWAS PARTISIPATIF DALAM PEMILU DAN PEMILIHAN 2024 - Ginanjar Andiraharja, Diyar (Bawaslu Provinsi Jawa Barat, 2021)
Political participation is the activity of individuals or groups that participate actively in politics by electing state leaders directly or indirectly, as well as inuencing government policies. The Election Supervisory Agency (Bawaslu) decision to invite youth to participate in quality democracy is an important breakthrough for the Election Supervisory Agency (Bawaslu). This paper uses qualitative analysis and library methods to analyze secondary data by elaborating on relevant materials, both primary and secondary. The conclusion of this paper is that the Participatory Supervisory Cadre is an investment by the Election Supervisory Agency (Bawaslu) in youth as an effort to build hope for a better quality democracy in the general election. Furthermore, the political participation of the Participatory Supervisory Cadre (SKPP) participants in the context of the 2020 election has been proven by their role as reporters and initial information providers. This indicates that the Participatory Supervisory Cadre (SKPP) is well-versed in electoral regulations and has made a genuine contribution to electoral law enforcement.